ERRATUM: Effects of combined endurance and resistance training in Amyotrophic Lateral Sclerosis: A pilot, randomized, controlled study - Antonio Merico; Marianna Cavinato; Caterina Gregorio; Alessandra Lacatena; Elisabetta Gioia; Francesco Piccione; Corrado Angelini (European Journal of Translational Myology, 2018)
Not available.